Implementation of Risk Management and The Effect on Performance Improvement in PT Krakatau Steel - Rahmat, Budi; Wiryono, Sudarso Kaderi (The Indonesian Journal of Business Administration, 2013)
Changes in the business environment is increasingly rapidly with increasing competition levels cause the appearance of a variety of business risks that could affect the company's performance. Efforts to secure the achievement of the goals and targets of the business, these risks need to be managed in a systematic, continuous and integrated. Application of the concept of risk management should be integrated with the company's strategy and performance management for all strategic plans, tactical plans and operational plans contain inherent risks that need to be managed properly. Through the Ministerial Regulation No. SOE. PER-01/MBU/2011, Minister of state mandates that all state-owned building and implementing risk management programs in an integrated corporation which is an integral part of the practice of good corporate governance. The final project is a review of the application of the concept of risk management in PT Krakatau Steel (Persero) Tbk., Evaluating its impact on corporate performance, analyze the causes of the problems and propose improvements necessary for the application of the concept of risk management had a positive impact on the effectiveness of the achievement of corporate goals. Based on the review and evaluation, it is known that the application of risk management in PT Krakatau Steel (Persero) Tbk. has not been implemented uniformly by all organizational units. In most of the organizational unit, found the lack of continuity between the risk management cycle. Process repeated measurements of risk level has not been run periodically, so the effectiveness of the risk mitigation measures that do not scalable. Risk identification process is not yet aligned with efforts to secure the achievement of predetermined performance targets. Therefore, the application of risk management to be integrated with the company's performance management system.Â Keywords: PT Krakatau Steel, risk, risk level, risk mitigation, key performance indicators.